The Seedling Nursery Survey on Leyte Island, the Philippines - Gregorio, Nestor; Harrison, Steve; Herbohn, John (Annals of Tropical Research, 2010)
Private and government nurseries in the Philippines are not delivering high quality planting materials of a wide species base for smallholder forestry, tree farming and reforestation programs in the country. A project supported by the Australian Centre for International Agricultural Research (ACIAR) has been conducted to improve the operational effectiveness of the forest nursery sector in the Philippines. Surveys involving personal interviews of nursery operators, observations of the nursery design and facilities and assessment of seedling quality have been undertaken in Leyte (reported in this paper) and Mindanao to provide baseline information for designing possible interventions. The Leyte study revealed that the low operational effectiveness of forest nurseries in a result of a combination of social, economic, technical and political factors. The majority of private nurseries are managed by resource-constrained smallholders with little access to high quality seedling production technologies. Seedling production, both in private and government nurseries, is largely quantity-oriented and the pathway of high quality germplasm is not well developed. Government nurseries operate to provide free seedlings but this scheme results in crowding out the small-scale private nurseries, reducing the operational effectiveness of the forest nursery sector in the Philippines requires policy changes to re-organize the operation of private and government nurseries and to strengthen the implementation of existing policies regulating the quality of planting stock from the forest nursery sector.